1999
DOI: 10.1136/gut.45.2008.ii25
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of the functional gastrointestinal disorders

Abstract: The functional gastrointestinal disorders (FGID) are the most frequent conditions seen in gastroenterology practice and comprise a major portion of primary care. Psychosocial factors are important in these disorders with regard to: (1) their eVects on gut physiology; (2) their modulation of the symptom experience; (3) their influence on illness behavior; (4) their impact on outcome; and (5) the choice of the therapeutic approach. This paper provides a review and consensus of the existing literature by gastroen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
287
0
32

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(327 citation statements)
references
References 20 publications
8
287
0
32
Order By: Relevance
“…Psychological distress has been widely accepted as an important factor of FD (Haug et al, 1995;Drossman et al, 1999;Locke et al, 2004). Several studies showed that the anxiety, depression and somatoform disorders were the most common psychiatric problems found in patients with FD (Magni et al, 1987;Haug et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological distress has been widely accepted as an important factor of FD (Haug et al, 1995;Drossman et al, 1999;Locke et al, 2004). Several studies showed that the anxiety, depression and somatoform disorders were the most common psychiatric problems found in patients with FD (Magni et al, 1987;Haug et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Th is study used a standard questionnaire to assess Valsalva maneuver-related activities including constipation ( 15 ), vomiting ( 16 ), and cough ( 17 ), and also assess alcohol consumption ( 18 ) and use of NSAID ( 13,14 ) in the week preceding inclusion in the study. A trained study nurse, who was blinded to the results of the endoscopy, met all subjects within 24 h post-endoscopy to provide instructions to complete the questionnaire.…”
Section: Data Collectionmentioning
confidence: 99%
“…Constipation was defi ned according to the modifi ed Rome II criteria ( 15 ) and was diagnosed if subjects had at least two of the following constipation symptoms in the week directly preceding the study: straining, lumpy or hard stool, sensation of incomplete evacuation, sensation of anorectal obstruction / blockage, or manual maneuvers to facilitate defecation during at least 25 % of defecations or fewer than three defecations per week. Severity of constipation was indicated by calculation of a symptom score based on the number of constipation symptoms.…”
Section: Assessment Of Constipationmentioning
confidence: 99%
“…FD is a disorder in which upper abdominal symptoms occur in the absence of organic disease that explains them (5). Patients with FD complain of meal-induced dyspeptic symptoms such as postprandial fullness and early satiation, and/or epigastric pain or burning sensation according to the Rome III criteria (5). IBS is characterized by abdominal pain or discomfort, and is associated with disturbed defecation (5).…”
Section: Introductionmentioning
confidence: 99%
“…GERD is caused by an abnormal reflux of gastric contents into the esophagus and is characterized by bothersome symptoms such as heartburn and acid regurgitation (4). FD is a disorder in which upper abdominal symptoms occur in the absence of organic disease that explains them (5). Patients with FD complain of meal-induced dyspeptic symptoms such as postprandial fullness and early satiation, and/or epigastric pain or burning sensation according to the Rome III criteria (5).…”
Section: Introductionmentioning
confidence: 99%